ASH-SHULH AS AN ATTEMPT OF SHARIA MICROFINANCE INSTITUTIONS TO SOLVE SHARIA ECONOMIC DISPUTES IN MADURA SOCIETY - Hariyanto, Erie; Harisah, Harisah; Hamzah, Moh; Faidi, Ach.; Umam, Hoirul (Jurisdictie: Jurnal Hukum dan Syariah, 2021)
The disputes resolution in the sharia financial institution gives opportunity and challenge for the Religious Court. Society tends to use ash-shulh by conducting deliberation in solving every dispute. This dispute resolution is taken because of the given legal freedom for society. Its purpose is to analyze the information on opportunities and challenges of the Religious Court as the judicial institution that has absolute authority in solving sharia economic disputes. This is qualitative research by studying secondary data and doing online and offline interviews with the informant. The Religious Court also plays a role in solving the disputes in the sharia microfinance institutions which generally choose the alternative way in disputes resolution by doing the negotiation. The study reveals that the sharia microfinance institutions depend on alternative ways in their dispute resolution such as negotiation and mediation by involving religious figures like Kyai. Madura society puts their trust in the religious figures more than the official institutions appointed in the Supreme Court Regulation No. 1 of 2016 concerning the Mediation in Court. However, the disputes resolution taken by society with the involvement of Kyai, is still based on the decree of the Religious Court in solving sharia disputes as a legal reference and a procedure taken by the judges.Penyelesaian sengketa di lembaga keuangan syariah memberikan peluang dan tantangan tersendiri bagi Pengadilan Agama. Masyarakat memiliki kecenderunganÂ menggunakan ash-shulh dengan cara musyawarah mufakat dalam menyelesaikan setiap sengketa. Upaya penyelesaian sengketa ini dipilih karena kebebasan hukum bagi masyarakat untuk memilih jalan penyelesaian sengketa. Penelitian ini dilakukan dengan menggunakan metode kualitatif melalui data sekunder serta wawancara kepada informan, baik secara online maupun offline. Hasil dan pembahasan menunjukkan bahwa lembaga keuangan mikro syariah memilih jalur alternatif penyelesaian sengketa seperti perundingan dan mediasi dengan melibatkan melibatkan seorang tokoh agama seperti Kyai. Masyarakat Madura lebih percaya terhadap tokoh agama dibandingkan lembaga resmi yang telah ditetapkan oleh Peraturan Mahkamah Agung Nomor 1 tahun 2016 tentang Mediasi di Peradilan. Namun, penyelesaian sengketa yang diambil masyarakat dengan melibatkan Kyai, tetap mengacu pada keputusan pengadilan agama dalam menyelesaikan sengketa syariah sebagai acuan hukum dan cara yang diambil oleh para hakim.